Evaluation of the 5-day vs. 7-day Co-Synch + CIDR protocol in dairy heifers using timed AI. - Mellieon, Harold Irvin Jr. (Kansas State University, 2011)
Our objectives were to determine: the effectiveness of upfront PGF2α injection to regress the corpus luteum; ovulation response to GnRH; and pregnancy outcomes. Dairy heifers (n = 545) from three locations (Florida, Kansas, and Mississippi) were assigned randomly to each of two treatments: 1) 25 mg of PGF2α injection and insertion of previously used autoclaved CIDR on d 7 followed by 100 µg of GnRH administered on d 5, and a 25 mg PGF2α injection at CIDR removal (7D) on d 0; 2) 100 µg of GnRH and insertion of previously used autoclaved CIDR on d 5 and 25 mg of PGF2α injection at CIDR removal (5D) on d 0. Artificial insemination (AI) occurred after detected estrus from d 0 to 3. Those heifers not detected in estrus were inseminated on d 3 and given a second 100 µg of GnRH. Blood collected on d 7 and 5 was assayed to determine concentrations of progesterone, presence of a CL (progesterone ≥1 ng/mL) on d 7, and whether luteolysis occurred in 7D heifers. Blood progesterone concentration from d 0 and 3 determined if luteolysis occurred in all heifers. Ovarian structure maps on d 5 and 0 were used to determine ovulation in response to GnRH on d 5. Pregnancy was determined on d 32 and 60 and intervening pregnancy loss was calculated. Of those heifers in the 7D treatment having progesterone ≥1 ng/mL on d 7, the proportion having progesterone <1 ng/mL 2 d later (luteolysis) was greater (P < 0.05) than that in the 5D treatment (43.0 vs. 22.9%, respectively). Total proportion of follicles that ovulated per heifer was numerically greater in the 7D treatment but only differed (P < 0.05) between locations. A treatment x location interaction was detected for pregnancy rates per AI. The Kansas location had no detectable treatment differences. In contrast, the 7D treatment produced greater (P < 0.05) pregnancy rates in the first replicate of the Florida location and at the Mississippi location. We concluded that the 5D protocol was not effective in producing acceptable luteolysis, pregnancy, and ovulation rates in comparison with the modified 7D protocol.
Keywords: Heifers; CIDR; Artificial insemination; Synchronization; Agriculture, General (0473); Animal Sciences (0475)